A review of thermal interface material fabrication method toward enhancing heat dissipation. (20th October 2020) - Bahru, Raihana; Zamri, Mohd Faiz Muaz Ahmad; Shamsuddin, Abd Halim; Shaari, Norazuwana; Mohamed, Mohd Ambri
Summary: Thermal interface materials (TIMs) are applied in electronic devices that are involved in heat generation and raising the temperature. The optimization of TIMs is important in heat dissipation to maintain the good performance of devices, low power during operation, and reduced internal damages among small components. The TIMs are inserted between two contact surfaces to enhance thermal conductivity that will reduce the increment of surface temperature in a longer time and facilitates the cooling process with a consistent power supplied to the system with minimum increment. Research on nanomaterials and hybrid materials aims to obtain maximum thermal conductivity and reduce resistance in the devices. However, the suitable fabrication method for achieving good production and performance is still debatable. Therefore, significant fabrication methods have been explored for various materials. This review provides insights into the current work focusing on the materials used in the development of TIMs by various methods. The discussion begins with the introduction of thermal management and the working principles applied in the system. Then, the methods applied for material fabrication into TIMs, including the advantages and disadvantages of the methods, are discussed. Last, the current challenges and opportunities in methods used are discussed to offer new inputs and improvement in method modification for TIMs design. The targeted thermal performance for the industrial market of TIMs for nanomaterial applications is approximately 100 W/mK and 1 × 10 −6 m 2 /WK with lowest power of 100 W. Abstract : The optimization of the fabrication method of TIMs is important to maintain the good performance of devices. Effective fabrication methods of TIM have been explored for various materials. This review provides insights into the current work focusing on the materials used in the development of TIMs by various methods, including the advantages and disadvantages. The targeted thermal performance for TIMs' industrial market for nanomaterial applications is approximately 100 W/mK and 1×10 −6 m 2 /WK with the lowest power of 100 W.